Stress and psychological well being in UK and Malaysian firefighters - Mohd Dahlan A. Malek; Rhona Flin (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to examine the relationship among sources of stress, coping strategy, job satisfaction and psychological well‐being and to examine the roles of coping behaviour as the moderator variable.